Immune modulation during anti-cancer radio(immuno)therapy - Irianto, Teresa Tamara; Gaipl, Udo; Rückert, Michael (International Review of Cell and Molecular Biology, 2023)
Cancer can affect all human organs and tissues and ranks as a prominent cause of death as well as an obstruction to increasing life expectancy. A notable breakthrough in oncology has been the inclusion of the immune system in fighting cancer, potentially prolonging life and providing long-term benefits. The concept of “immunotherapy” has been discussed from the 19th and early 20th centuries by Wilhelm Busch, William B. Coley and Paul Ehrlich. This involves distinct approaches, including vaccines, non-specific cytokines and adoptive cell therapies. However, despite the advances made in recent years, questions on how to select the best therapeutic options or how to select the best combinations to improve clinical outcomes are still relevant for scientists and clinicians. More than half of cancer patients receive radiotherapy (RT) as part of their treatment. With the advances in RT and immunotherapy approaches, it is reasonable to consider how to enhance immunotherapy with radiation and vice versa, and to investigate whether combinations of these therapies would be beneficial. In this chapter, we will discuss how the immune system responds to cancer cells and different cancer therapies with a focus on combination of RT and immunotherapy (radioimmunotherapy, RIT).
CRIS-Team Scopus Importer:2023-08-11
Keywords: Immune checkpoint molecules; Immune editing; Immunogenic cell death; Radioimmunotherapies; Radiotherapy